Copper tailing autoclaved aerated concrete and preparation method thereof

By using copper -tailed ore as a silicon raw material in the steaming pressure of copper -tailed ore, and combined with the rosin hot polymer air induction, polycarboxylic acid hydraulic agent, nanomaterial and calcium silicate gel nano composite material , Optimize the air -to -gas air rate and thickness rate, solve the problem of low compressive strength and poor insulation performance of copper -tail ore steaming pressure, and realize the efficient utilization of copper tail ore and the decrease in environmental pollution.

CN119330660APending Publication Date: 2025-01-21ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366034.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Copper tailings autoclaved aerated concrete has problems of low compressive strength and poor insulation performance. At the same time, the environmental pollution risk of copper tailings is high and the utilization rate is low.

Method used

By using copper tailings as siliceous raw material, combined with rosin thermopolymer air-entraining agent and polycarboxylate water-reducing agent, nanomaterials and hydrated calcium silicate gel nanocomposites, the gas generation rate and thickening of the slurry are optimized. rate, enhancing the uniformity of pore structure and pore wall strength.

Benefits of technology

Significantly improve the compressive strength and thermal insulation performance of copper tailings autoclaved aerated concrete, achieve efficient utilization of copper tailings, and reduce the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides copper tailing autoclaved aerated concrete and a preparation method thereof, and relates to the field of concrete preparation. The concrete is prepared from copper tailings, an alkali activator, gypsum, quicklime, cement, a rosin thermal polymer air entraining agent, a polycarboxylate superplasticizer, a nano material and a seed crystal. The copper tailings are used as a siliceous raw material, the solid waste utilization rate is greatly increased, the rosin thermopolymer air entraining agent and the polycarboxylate superplasticizer are combined, the gas forming rate and the thickening rate of slurry are optimized, the uniformity of a pore structure is improved, meanwhile, the nano material and the seed crystal are added, the silicon-calcium hydrothermal synthesis reaction of the test block is further promoted, and the comprehensive performance of the test block is improved. The strength of the pore wall is enhanced, so that the pore structure is more stable, and the thermal insulation property and compressive strength of the copper tailing autoclaved aerated concrete block are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete preparation, and in particular to copper tailings autoclaved aerated concrete and a preparation method thereof. Background Art

[0002] Autoclaved aerated concrete is a lightweight and porous building material with low density, good thermal insulation performance and certain strength. It is made of siliceous and calcareous materials as the main raw materials, mixed with gas-generating agents, stirred with water, and formed voids by chemical reactions, and then processed by static curing, demoulding cutting, autoclaving and other processes. However, copper tailings autoclaved aerated concrete has problems such as low compressive strength and poor thermal insulation performance.

[0003] Copper tailings are a type of waste material generated during the beneficiation of copper ore. Most copper tailings are stored in the open air in the form of tailings ponds, which not only occupies a large amount of land resources, but also may cause safety accidents such as dam breaches. At the same time, copper tailings have the risk of excessive leaching of heavy metal ions such as Cu, which can easily cause soil and water pollution. Therefore, how to apply copper tailings to the preparation of autoclaved aerated concrete is an important direction at this stage. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a copper tailings autoclaved aerated concrete and a preparation method thereof, which can process a large amount of copper tailings, a solid waste that is harmful to the environment, and at the same time improve the compressive strength and thermal insulation performance of the copper tailings autoclaved aerated concrete. The technical problems of low comprehensive utilization rate of copper tailings, environmental pollution, low compressive strength and poor thermal insulation performance of copper tailings autoclaved aerated concrete are solved, and the sustainable utilization of industrial solid waste is achieved.

[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0006] A copper tailings autoclaved aerated concrete comprises the following raw materials in parts by weight: 35-50 parts of copper tailings, 0.3-0.5 parts of alkali activator, 10-25 parts of gypsum, 5-20 parts of quicklime, 10-25 parts of cement, 0.01-0.03 parts of rosin thermopolymer air entraining agent, 0.1-0.2 parts of polycarboxylic acid water reducer, 0.1-0.2 parts of nano material and 0.1-0.2 parts of seed crystal; and the seed crystal is a hydrated calcium silicate gel nano composite material with a solid content of ≥10% and a particle size of ≤40nm.

[0007] Preferably, the SiO2 content in the copper tailings is above 55%, the Al2O3 content is 8%-12%, and the MgO content is 20%-30%.

[0008] Preferably, the cement is P·O52.5 ordinary Portland cement, and its specific surface area is 450-600m 2 / kg.

[0009] Preferably, the alkaline activator is anhydrous sodium silicate.

[0010] Preferably, the polycarboxylate water-reducing agent has a purity of 98%±1% and a solution viscosity of 1500-5000 mPa·s.

[0011] Preferably, the rosin thermopolymer air-entraining agent is a PC-2 rosin thermopolymer air-entraining agent, and has a pH value of 12.2, a chloride ion content of 0%, a total alkali content of 0.68%, a foaming degree of 45%, a water bleeding rate of 50.8%, a water reduction rate of 7.5%, and an air content of 4.4%.

[0012] Preferably, the nano material is silicon dioxide, the purity of which is ≥99% and the average particle size is ≤20 nm.

[0013] The preparation method of copper tailings autoclaved aerated concrete comprises the following steps:

[0014] (1) mixing copper tailings, nanomaterials, and seed crystals to obtain a mixed material;

[0015] (2) Grind the mixture to a Blaine surface area of ​​450 to 750 m 2 / kg; while grinding, introduce the alkali activator in solid form, mix evenly to make high-activity copper tailings powder for use;

[0016] (3) Mix the rosin thermal polymer air entraining agent and the polycarboxylic acid water reducer with warm water, and stir with a glass rod for 1 minute to prepare a mixed solution for use;

[0017] (4) putting high-activity copper tailings powder, gypsum, and part of the mixed liquid into a mixer and mixing them evenly, then adding cement and the remaining mixed liquid and mixing them evenly, then adding quicklime and mixing them evenly again to obtain a slurry for standby use;

[0018] (5) Inject the slurry into the mold, cover it with a protective film and place it in a static room with a temperature of 45-55°C and a humidity of 55-70% for static curing for 2-4 hours;

[0019] (6) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 to -0.07 MPa and 180 to 190°C for 6 to 10 hours. After being taken out of the autoclave, it is naturally cured to obtain autoclaved aerated concrete.

[0020] Preferably, the warm water in step (3) is 45° C. ordinary water.

[0021] Preferably, in step (5), the water-to-solid ratio of the slurry injected into the mold is controlled to be 0.6-0.65.

[0022] The present invention provides a copper tailings autoclaved aerated concrete and a preparation method thereof, which has the following advantages over the prior art:

[0023] The present invention uses copper tailings as siliceous raw materials, greatly improves the utilization rate of solid waste, adopts a combination of rosin thermal polymer air entraining agent and polycarboxylic acid water reducer, optimizes the gas evolution rate and thickening rate of slurry, and improves the uniformity of pore structure. At the same time, nano materials and crystal seeds are added to further promote the hydrothermal synthesis reaction of silicon calcium in the test block, enhance the pore wall strength, make the pore structure more stable, and improve the thermal insulation performance and compressive strength of the copper tailings autoclaved aerated concrete block. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The raw materials of the following examples and comparative examples are selected as follows:

[0026] Copper tailings: taken from the Dongguashan copper mine tailings, with SiO2 content above 55%, Al2O3 content around 10%, and MgO content around 25%;

[0027] The cement is P·O52.5 ordinary Portland cement, with a specific surface area of ​​450-600m 2 / kg;

[0028] Anhydrous sodium silicate: Sinopharm Chemical Reagent Co., Ltd.;

[0029] Polycarboxylate water reducer: milky white liquid, purity is (98±1)%, solution viscosity is 1500~5000mPa·s, from Sanxi Feike New Material Technology Co., Ltd.;

[0030] The rosin thermopolymer air-entraining agent adopts PC-2 rosin thermopolymer air-entraining agent produced by Qingdao Keli Building Materials Co., Ltd., with a pH value of 12.2, a chloride ion content of 0%, a total alkali content of 0.68%, a foaming degree of 45%, a water bleeding rate of 50.8%, a water reduction rate of 7.5%, and an air content of 4.4%;

[0031] Hydrated calcium silicate gel nanocomposite material: produced by Subot New Materials Co., Ltd., with a mass concentration of 40%;

[0032] Nano-silicon dioxide: purity ≥99%, average particle size ≤20nm.

[0033] Embodiment 1:

[0034] Preparation of copper tailings autoclaved aerated concrete:

[0035] (1) Material preparation: 35 parts of copper tailings, 0.3 parts of anhydrous sodium silicate, 10 parts of gypsum, 5 parts of quicklime, 10 parts of cement, 0.01 parts of rosin thermopolymer air entraining agent, 0.1 parts of polycarboxylic acid water reducer, 0.1 parts of nano-silica, and 0.1 parts of hydrated calcium silicate gel nanocomposite material;

[0036] (2) mixing copper tailings, nano-silicon dioxide, and hydrated calcium silicate gel nano-composite solids;

[0037] (3) Grind the mixture to a Blaine surface area of ​​650 m 2 / kg; while grinding, anhydrous sodium silicate is introduced in solid form and mixed evenly to produce high-activity copper tailings powder;

[0038] (4) Mix the rosin thermal polymer air entraining agent and the polycarboxylic acid water reducer with 45°C warm water and stir with a glass rod for 1 minute to prepare a mixed solution;

[0039] (5) putting high-activity copper tailings powder, gypsum, and part of the mixed liquid into a mixer and mixing them evenly, then adding cement and the remaining mixed liquid and mixing them evenly, adding quicklime, and mixing them evenly again to obtain a slurry, wherein the water-to-solid ratio of the slurry is 0.65;

[0040] (6) The slurry is injected into the mold, covered with a protective film, and sent to a static room with a temperature of 45°C and a humidity of 60% for static curing for 3 hours;

[0041] (7) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 MPa and 180°C for 8 h. After being taken out of the autoclave, it is naturally cured for 7 days to obtain autoclaved aerated concrete.

[0042] Embodiment 2:

[0043] Preparation of copper tailings autoclaved aerated concrete:

[0044] (1) Material preparation: 40 parts of copper tailings, 0.4 parts of anhydrous sodium silicate, 10 parts of gypsum, 5 parts of quicklime, 10 parts of cement, 0.02 parts of rosin thermopolymer air entraining agent, 0.2 parts of polycarboxylic acid water reducer, 0.15 parts of nano-silica, and 0.15 parts of hydrated calcium silicate gel nanocomposite material;

[0045] (2) mixing copper tailings, nano-silicon dioxide, and hydrated calcium silicate gel nano-composite solids;

[0046] (3) Grind the mixture to a Blaine surface area of ​​650 m 2 / kg; while grinding, anhydrous sodium silicate is introduced in solid form and mixed evenly to produce high-activity copper tailings powder;

[0047] (4) Mix the rosin thermal polymer air entraining agent and the polycarboxylic acid water reducer with 45°C warm water and stir with a glass rod for 1 minute to prepare a mixed solution;

[0048] (5) putting high-activity copper tailings powder, gypsum, and part of the mixed liquid into a mixer and mixing them evenly, then adding cement and the remaining mixed liquid and mixing them evenly, adding quicklime, and mixing them evenly again to obtain a slurry, wherein the water-to-solid ratio of the slurry is 0.65;

[0049] (6) The slurry is injected into the mold, covered with a protective film, and sent to a static room with a temperature of 45°C and a humidity of 60% for static curing for 3 hours;

[0050] (7) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 MPa and 180°C for 8 h. After being taken out of the autoclave, it is naturally cured for 7 days to obtain autoclaved aerated concrete.

[0051] Embodiment 3:

[0052] Preparation of copper tailings autoclaved aerated concrete:

[0053] (1) Material preparation: 50 parts of copper tailings, 0.5 parts of anhydrous sodium silicate, 25 parts of gypsum, 20 parts of quicklime, 10 parts of cement, 0.03 parts of rosin thermopolymer air entraining agent, 0.2 parts of polycarboxylic acid water reducer, 0.2 parts of nano-silica, and 0.2 parts of hydrated calcium silicate gel nanocomposite material;

[0054] (2) mixing copper tailings, nano-silicon dioxide, and hydrated calcium silicate gel nano-composite solids;

[0055] (3) grinding the mixture to a Blaine specific surface area of ​​650 m2 / kg; while grinding, introducing anhydrous sodium silicate in solid form, and mixing evenly to prepare a high-activity copper tailings powder;

[0056] (4) Mix the rosin thermal polymer air entraining agent and the polycarboxylic acid water reducer with 45°C warm water and stir with a glass rod for 1 minute to prepare a mixed solution;

[0057] (5) putting high-activity copper tailings powder, gypsum, and part of the mixed liquid into a mixer and mixing them evenly, then adding cement and the remaining mixed liquid and mixing them evenly, adding quicklime, and mixing them evenly again to obtain a slurry, wherein the water-to-solid ratio of the slurry is 0.65;

[0058] (6) The slurry is injected into the mold, covered with a protective film, and sent to a static room with a temperature of 45°C and a humidity of 60% for static curing for 3 hours;

[0059] (7) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 MPa and 180°C for 8 h. After being taken out of the autoclave, it is naturally cured for 7 days to obtain autoclaved aerated concrete.

[0060] Comparative Example 1:

[0061] Preparation of ordinary autoclaved aerated concrete:

[0062] (1) Ingredients: calculated by weight, 24 parts of fly ash, 30 parts of river sand, 10 parts of quicklime, 10 parts of cement, 0.3 parts of sodium silicate, 0.4 parts of aluminum powder, 5 parts of gypsum and 0.1 parts of sodium hexametaphosphate;

[0063] (2) Grinding and crushing fly ash and river sand by a ball mill, and obtaining a dry mixed material by screening;

[0064] (3) The dry mix, quicklime, cement and gypsum were mixed evenly in a mud slurry mixer, and then warm water at 58° C. was added and stirred rapidly for 1.5 minutes. Then, sodium silicate and aluminum powder were added in sequence and stirred rapidly for 30 seconds to obtain a uniform slurry with a water-to-cement ratio of 0.65;

[0065] (4) The obtained slurry is poured into a mold and allowed to stand for curing at 50°C for 5 hours. After the curing is completed, the mold is removed and the product is placed in an autoclave at 1.05MPa and 185°C for further autoclaving for 7 hours. Finally, the product is dried to obtain an autoclaved aerated concrete block.

[0066] Comparative Example 2:

[0067] Preparation of ordinary autoclaved aerated concrete:

[0068] (1) Ingredients: 20 parts of copper tailings, 40 parts of river sand, 10 parts of quicklime, 16 parts of cement, 0.7 parts of sodium silicate, 0.7 parts of aluminum powder, 5 parts of gypsum, and 0.1 parts of sodium hexametaphosphate;

[0069] (2) grinding and crushing the copper tailings and river sand in turn by a ball mill, and obtaining a dry mixed material after screening;

[0070] (3) The dry mix, quicklime, cement and gypsum were mixed evenly in a mud slurry mixer, and then 58°C warm water was added and stirred rapidly for 1.5 min. After stirring, sodium silicate and aluminum powder were added in sequence and stirred rapidly for 30 s to obtain a uniform slurry with a water-to-solid ratio of 0.65;

[0071] (4) pouring the obtained slurry into a mold and curing it at 50°C for 5 hours; after the curing is completed, demoulding it and placing it in a 1.05MPa, 185°C autoclave for further autoclaving for 7 hours; after the curing is completed, drying is carried out to obtain an autoclaved aerated concrete block.

[0072] Comparative Example 3:

[0073] Preparation of copper tailings autoclaved aerated concrete:

[0074] (1) The raw material ratio is the same as that in Example 1;

[0075] (2) grinding the copper tailings with a ball mill for mechanical activation;

[0076] (3) uniformly mixing the mixed solution, activated copper tailings powder, quicklime, gypsum and cement, then adding nano-silicon dioxide, hydrated calcium silicate gel nanocomposite material and anhydrous sodium silicate, stirring uniformly to obtain a slurry, wherein the water-to-cement ratio of the slurry is 0.6;

[0077] (4) The slurry is injected into the mold, covered with a protective film, and sent to a static room with a temperature of 55°C and a humidity of 70% for static curing for 2 hours;

[0078] (5) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 MPa and 180°C for 6 hours. After being taken out of the autoclave, it is naturally cured for 7 days to obtain autoclaved aerated concrete.

[0079] Quality Inspection:

[0080] Referring to GB / T11969-2020 "Autoclaved Aerated Concrete Performance Test Method" and GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method" standards, the autoclaved aerated concrete prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the specific results are shown in the following table:

[0081]

[0082] It can be seen from the above table:

[0083] (1) The autoclaved aerated concrete in Examples 1-3 performed well in all aspects, especially in terms of compressive strength and thermal insulation performance, indicating that the addition of rosin thermopolymer air-entraining agent combined with polycarboxylic acid water-reducing agent optimized the gas evolution rate and thickening rate of the slurry, improved the pore uniformity and pore structure, and enhanced the pore wall strength by adding nano-sodium silicate and seed crystals, thereby improving the quality of the autoclaved aerated concrete;

[0084] (2) The autoclaved aerated concrete in Comparative Example 3 is weaker than that in the embodiment in terms of strength and thermal insulation, indicating that the copper tailings after mechanical activation are less active than those after mechanical-chemical coupling activation in the embodiment, resulting in poor hydration reaction and low pore wall strength. At the same time, the mixed liquid made of rosin thermopolymer air-entraining agent and polycarboxylic acid water-reducing agent is not added in stages, and the slurry gas evolution rate and thickening rate do not match, resulting in poor uniformity of the pore structure. Therefore, the obtained autoclaved aerated concrete has poor compressive strength and thermal insulation performance.

[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A copper tailings autoclaved aerated concrete, characterized in that: The copper tailings autoclaved aerated concrete comprises the following raw materials in parts by weight: 35-50 parts of copper tailings, 0.3-0.5 parts of alkali activator, 10-25 parts of gypsum, 5-20 parts of quicklime, 10-25 parts of cement, 0.01-0.03 parts of rosin thermopolymer air entraining agent, 0.1-0.2 parts of polycarboxylic acid water reducer, 0.1-0.2 parts of nano material and 0.1-0.2 parts of seed crystal; and the seed crystal is a hydrated calcium silicate gel nano composite material with a solid content of ≥10% and a particle size of ≤40nm.

2. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The SiO2 content in the copper tailings is above 55%, the Al2O3 content is 8%-12%, and the MgO content is 20%-30%.

3. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The cement is P·O52.5 ordinary Portland cement, and its specific surface area is 450-600m 2 / kg.

4. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The alkaline activator is anhydrous sodium silicate.

5. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The polycarboxylate water-reducing agent has a purity of 98%±1% and a solution viscosity of 1500-5000 mPa·s.

6. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The rosin thermopolymer air-entraining agent is a PC-2 rosin thermopolymer air-entraining agent, and has a pH value of 12.2, a chloride ion content of 0%, a total alkali content of 0.68%, a foaming degree of 45%, a water bleeding rate of 50.8%, a water reduction rate of 7.5%, and an air content of 4.4%.

7. The copper tailings autoclaved aerated concrete according to claim 1, characterized in that: The nano material is silicon dioxide, the purity of which is ≥99% and the average particle size is ≤20nm.

8. A method for preparing copper tailings autoclaved aerated concrete as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing copper tailings, nanomaterials, and seed crystals to obtain a mixed material; (2) Grind the mixture to a Blaine surface area of ​​450 to 750 m 2 / kg; while grinding, introduce the alkali activator in solid form, mix evenly to make high-activity copper tailings powder for use; (3) Mix the rosin thermal polymer air entraining agent and the polycarboxylic acid water reducer with warm water, and stir with a glass rod for 1 minute to prepare a mixed solution for use; (4) putting high-activity copper tailings powder, gypsum, and part of the mixed liquid into a mixer and mixing them evenly, then adding cement and the remaining mixed liquid and mixing them evenly, then adding quicklime and mixing them evenly again to obtain a slurry for standby use; (5) Inject the slurry into the mold, cover it with a protective film and place it in a static room with a temperature of 45-55°C and a humidity of 55-70% for static curing for 2-4 hours; (6) After the static curing is completed, the mold is removed and the resulting blank is placed in an autoclave for autoclaving at -0.06 to -0.07 MPa and 180 to 190°C for 6 to 10 hours. After being taken out of the autoclave, it is naturally cured to obtain autoclaved aerated concrete.

9. The preparation method according to claim 8, characterized in that: The warm water in step (3) is 45° C. ordinary water.

10. The preparation method according to claim 8, characterized in that: In the step (5), the water-to-solid ratio of the slurry injected into the mold is controlled to be 0.6-0.65.